Actaea racemosa L. Rhizome Protect against MPTP-Induced Neurotoxicity in Mice by Modulating Oxidative Stress and Neuroinflammation - Marika Cordaro; Ramona D'Amico; Roberta Fusco; Tiziana Genovese; Alessio Filippo Peritore; Enrico Gugliandolo; Rosalia Crupi; Davide Di Paola; Livia Interdonato; Daniela Impellizzeri; Salvatore Cuzzocrea; Rosanna Di Paola; et al. (MDPI AG, 2022)
Parkinson's disease (PD) is a dopaminergic neuron-related neurodegenerative illness. Treatments exist that alleviate symptoms but have a variety of negative effects. Recent research has revealed that oxidative stress, along with neuroinflammation, is a major factor in the course of this disease. Therefore, the aim of our study was to observe for the first time the effects of a natural compound such as Actaea racemosa L. rhizome in an in vivo model of PD induced by neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). For the study, mice received four injections of MPTP (20 mg/kg) for the induction of PD. Starting 24 h after the first administration of MPTP we treated mice with Actaea racemosa L. rhizome (100 mg/kg) daily for seven days. Our findings clearly demonstrated that Actaea racemosa L. rhizome treatment decreases oxidative stress by activating redox balance enzymes such as Nrf2/HO-1. We also demonstrated that Actaea racemosa L. rhizome is capable of modulating inflammatory indicators involved in PD, such as IκB-α, NF-κB, GFAP and Iba1, thus reducing the degeneration of dopaminergic neurons and motor and non-motor alterations. To summarize, Actaea racemosa L. rhizome, which is subject to fewer regulations than traditional medications, could be used as a dietary supplement to improve patients' brain health and could be a promising nutraceutical choice to slow the course and symptoms of PD.